Labour productivity, environmental quality and infrastructure in Bangladeshi readymade garments industry - Khuky, Mahmuda Akter (2021)
Bangladesh is the second top readymade garments (RMG) exporting country, and the RMG industry plays a vital role in the remarkable economic growth of the country. Despite the stupendous growth of the RMG industry and its bright prospects, challenges are still there. This study, therefore, examines the relationship between RMG export, labour productivity, and economic growth in Bangladesh. The first objective used Autoregressive Distributed Lag (ARDL) method for analysis with a time-series data from 1983 to 2019. The result of the first objective found that a long run positive relationship between RMG export, labour productivity, and economic growth is observed. The policy implications suggest improving the labour skills, providing training, and the use of information technology to the RMG sector will promote economic growth. Secondly, this study investigated the impact RMG industry on environmental quality under a dynamic Environmental Kuznets Curve (EKC) context. The second objective also utilised Autoregressive Distributed Lag (ARDL) method is used to analyse time-series data from 1983 to 2019. The findings of the study have demonstrated a positive significant determinant of RMG export on CO2 emission in Bangladesh. The study recommended the regulators should introduce more environmentally friendly ways of production. By initiating a cleaner production and considering the energy consumption and economic growth should be considered to reduce CO2 dioxide emissions. This finding suggests policy action should prioritize and make more investment to markedly address the CO2 emission issue. Thirdly, this study investigates the roles of transport and Information communication technology (ICT) in RMG exports. For third objective gravity model analysis has been used with pooled OLS and the Poisson-Pseudo Maximum Likelihood (PPML) estimators. Transport infrastructure is captured by four indicators. The results of this objective indicate that rail, air, and port-related infrastructure have positive and significant relationship with RMG exports. Thus, the results support the significance of transport infrastructure quality to boost RMG exports performance. The empirical findings suggest more investment in transportation facilities is vital. To measure ICT infrastructure, the current study used proxies such as fixed lines, mobile phone ii subscriptions, and internet users. The results provide empirical evidence of the positive effects of telecommunications on RMG exports. Therefore, ICT infrastructure found significant in boosting RMG exports in Bangladesh. In practice, the findings of this research reduce the scarcity of literature focusing on the components of labour productivity, environment and infrastructure that are crucial for RMG sector development. The findings of this study may serve as policy guidance to facilitate different crucial factors for achieving and maintaining the competitiveness of the RMG industry of Bangladesh.